Correlation of plain radiographic indices of the proximal femur with quantitative bone mineral density (bmd) - a study on patients treated for osteoporotic fractures. - Ibrahim, Nor Zarini Yusoff (2013)
Measurement of Bone Mineral Density (BMD) using Dual Energy X-ray Absorptiometry (DXA) is the accepted gold standard method to diagnose osteoporosis. Established positive correlation between the bone quality measured by DXA scan and the bone quantity assessment by plain radiograph will be beneficial in the absence of DXA scan facility as the routine hip radiographs can be used as the principle study by primary care providers and orthopedic specialists to support diagnosis, initiating treatment and monitoring the progression of the disease. This is a prospective cross sectional analytical study with aims to identify the correlation of plain radiographic indices of the proximal femur with the quantitative bone mineral density and to determine the sensitivity and specificity of the radiographic parameters to diagnose osteoporosis in subjects treated for fragility fractures in an institution. Plain hip radiographs of 64 patients admitted for fragility fractures were evaluated. Radiographic parameters including Dorr classification, canal- to- calcar ratio (CC) and cortical thickness index (CTI) were measured and compared with the hip and spine bone mineral density. The CTIs correlated positively with the spine and hip BMD for lateral radiograph (r = 0.604, r = 0.715, p < 0.0001) and for AP radiograph (r = 0.554, p < 0.001, r = 0.411, p = 0.001). The t- score of the femoral neck and the spine in type C proximal femur geometry was significantly lower than in type B geometry (p < 0.05). The threshold for canal to calcar ratio set at > 0.636 has the sensitivity of 65.1% and specificity of 52.4% to differentiate osteoporotic and non osteoporotic group. Type C femoral geometry has 62.8% sensitivity, 71.4% specificity and 2.2 positive likelihood ratio to represent osteoporosis. Hips with smaller lateral and AP cortical thickness indices had lower bone mineral density. Similarly, hips with larger canal-to-calcar ratio had lower bone mineral density. Canal-tocalcar ratio of 0.636 or more and Type C femoral geometry should alert the health care providers for further osteoporosis evaluation and initiation of treatment.